Three-year course of clinical high-risk symptoms for psychosis in the community: a latent class analysis - C. Michel; N. Osman; G. Rinaldi; B. G. Schimmelmann; J. Kindler; F. Schultze-Lutter (Epidemiology and Psychiatric Sciences)
Abstract Aims Clinical high-risk for psychosis (CHR-P) states exhibit diverse clinical presentations, prompting a shift towards broader outcome assessments beyond psychosis manifestation. To elucidate more uniform clinical profiles and their trajectories, we investigated CHR-P profiles in a community sample.